Pengembangan Tata Kelola Pelayanan Administrasi Desa Berbasis Digital Di Desa Molosipat Kecamatan Popayato Barat Kabupaten Pohuwato - Abdussamad, Zuchri; Tahir, Arifin (Universitas Negeri Gorontalo, 2024)
Digital systems with their various programs, such as websites, SMS Centres/Call Centres, e-papers, One-Stop Integrated Services (PTSP), e-ktp, e-planning, e-budgeting, e-procurement, e-warehouse can encourage increased transparency of village budget management, encourage the formation of comDEpliance with the law and strengthen legal certainty for village government officials in carrying out their duties. By implementing digital systems, work effectiveness and efficiency will increase. Digital systems that provide transparency can ultimately encourage an increase in the responsiveness of village government administrators and the community as the owner of sovereignty is also given the same space in obtaining services from village government officials. In Molosipat Village, West Popayato District, Pohuwato Regency, in carrying out administrative services, they still use conventional or manual methods so they are still less effective and efficient. The community often experiences difficulties when submitting letters that are limited by space and time, such as the community being required to go to the village office and can only be submitted during working hours. In addition, letter administration archives require a large storage capacity and are prone to physical file damage. Through the MBKM integrated KKN program in Molosipat Village in 2023, it aims to implement the digitalization of web-based administrative services to facilitate the community in accessing information and obtaining services in Molosipat Village. In addition, assistance in the use of the system is also provided to village government officials with training activities that include exposure and practice of system functionality.